Model expectations of public safety in microentrepreneurs in central Mexico - García Lirios, Cruz (DIXI, 2019)
Objective: to establish the reliability and validity of an instrument that measures expectations of public safety in a context of low local development. Methodology: a non-experimental study was carried out with a non-probabilistic selection of microentrepreneurs, considering their participation in business development and social entrepreneurship programs. Results: three factors related to recruitment, technology and training were established, which accounted for 74% of the total variation. Limitations: Design limits results to the search scenario. Study value: the instrument can be compared with other scenarios and study samples with similar conditions. Conclusions: an exploratory factorial structure was established that will allow its study from the inclusion and contrast of other variables such as quality of life and subjective well-being reported in the literature.